"I didn't think we'd be dealing with stuff like this": A qualitative study of volunteer support for very disadvantaged pregnant women and new mothers. (February 2017) - McLeish, Jenny; Redshaw, Maggie
Abstract: Objective: to identify the particular issues associated with volunteer support for very disadvantaged mothers (who were young, had insecure immigration status, were recent migrants whose English was poor, misused drugs or alcohol, or were involved in crime), from the perspective of the volunteers. Design: a qualitative descriptive study, informed by phenomenological social psychology. Semi-structured qualitative interviews were carried out between July 2013 and March 2015. Interview transcripts were analysed using inductive thematic analysis. Setting: nine volunteer support projects for pregnant women and new mothers, run by third sector organisations in England. Participants: 38 volunteer supporters. Measurements and findings: three key themes were identified: 'Meeting challenges', 'Needing support' and 'Identifying successes'. 'Meeting challenges' contained the subthemes 'making the relationship of trust', 'remaining non-judgemental', 'maintaining boundaries' and 'dealing with child protection'. 'Needing support' contained the subthemes 'feeling prepared', 'feeling supported' and 'staying safe'. 'Identifying successes' contained the subthemes 'celebrating the small wins', 'validation as a mother', and 'supporting access to services'. Key conclusions: volunteers were able to build strong, empowering relationships with some very disadvantaged women during pregnancy and afterwards, including where the mothers did not readily engage with professionals. However, supporting women with complex needs is emotionally challenging and volunteers need to be carefully selected, realistically trained and robustly supervised and supported during their volunteering. Implications for practice: third sector organisations offering volunteer support for pregnant women and new mothers can be valuable partners in reaching very disadvantaged women who may find it difficult to engage with services. Volunteers can build up a relationship of trust with vulnerable mothers over time, but need to be well supported to do this safely and effectively. Highlights: Volunteers worked with women who might be 'hard to reach' for services. Volunteers could build empowering relationships with very disadvantaged women. Supporting women with complex needs was emotionally challenging. Volunteers needed to be carefully selected, trained and supervised. The project co-ordinator had a vital role in supporting volunteers.